2002
DOI: 10.1136/bmj.325.7364.576
|View full text |Cite
|
Sign up to set email alerts
|

The mental health of UK Gulf war veterans: phase 2 of a two phase cohort study

Abstract: Most disabled Gulf veterans do not have a formal psychiatric disorder. Post-traumatic stress disorder is not higher in Gulf veterans than in other veterans. Psychiatric disorders do not fully explain self reported ill health in Gulf veterans; alternative explanations for persistent ill health in Gulf veterans are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
1
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(55 citation statements)
references
References 14 publications
3
50
1
1
Order By: Relevance
“…Large-scale studies of veterans of the 1991 Gulf War have found that the most common mental health problems are depression, anxiety disorders and alcohol misuse/dependence (Ismail 2002;Ikin 2004;Toomey 2007). A small cross-sectional study in the UK of Gulf, Bosnia and 'Era' (personnel who served in the military at the same time but were not deployed on these operations) veterans who had all left the military revealed the same findings (Iversen 2005b).…”
Section: Common Mental Health Problems In Veteransmentioning
confidence: 58%
“…Large-scale studies of veterans of the 1991 Gulf War have found that the most common mental health problems are depression, anxiety disorders and alcohol misuse/dependence (Ismail 2002;Ikin 2004;Toomey 2007). A small cross-sectional study in the UK of Gulf, Bosnia and 'Era' (personnel who served in the military at the same time but were not deployed on these operations) veterans who had all left the military revealed the same findings (Iversen 2005b).…”
Section: Common Mental Health Problems In Veteransmentioning
confidence: 58%
“…Furthermore, reports of pre-existing medical and psychiatric conditions, as well as other factors such as smoking and perceived military preparedness, were related to physical and mental health component summary scores. Several other subsequent studies of Gulf War veterans have had similar findings [2,4,5]. Additionally, patients seen in the VA medical system have lower SF-36 scores than patients who do not use the VA health care system [6], suggesting that this population may have compromised HRQoL.…”
Section: Introductionmentioning
confidence: 67%
“…In a previous study by Barrett et al [20], military veterans with PTSD reported lower HRQoL ratings than military veterans without PTSD. Ismail et al [4] also found a relationship between psychiatric distress and disability among Gulf War I veterans from the U.K., although the association was weak. The additional impairment imposed by coexisting mental disorders that span two or more mental disorder categories has not been determined.…”
Section: Introductionmentioning
confidence: 92%
“…Estos trabajos han demostrado que por ejemplo el personal militar que ha estado en situación de guerra tiene más riesgo de tener problemas de salud física (1,33) y de salud mental (10,16,25,50,51). Con respecto a calidad de vida se ha encontrado que en general es más pobre (42,43).…”
Section: Discussionunclassified